(untitled) (Bangladesh Journal of Zoology, 2018)
A total of 66 (sixty-six) fresh fecal samples were collected during July 2017 to October 2018 from rhesus macaques (Macaca mulatta) residing in Bangladesh National Zoo, Dhaka. Samples were analyzed applying formol-ether concentration technique. All the rhesus macaques, irrespective of age and sex, were found to be infested with one or more species of gastrointestinal (GI) helminth parasites. Ascaris spp. was noticed in all the fecal samples. Overall intensity of helminths was higher in male (38.53) that in female (31.04) comprising the maximum (58.08) in adult male (p < 0.005). The highest intensity was of Ascaris spp. (3.33 ± 1.39) and found in adult male hosts. Young female rhesus macaques displayed the maximum intensity of Trichuris spp. (3.56 ± 0.73). Bangladesh J. Zool. 46(2): 231-237, 2018